Analisis Pengaruh Implementasi Key Performance Indicator (KPI) dan Beban Kerja Terhadap Turnover Intention di PT Cemerlang Hajar Aswad Tour & Travel Gresik - Vina Miladiyah; Roziana Ainul Hidayati (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
Employee turnover is a strategic issue in human resource management because it affects the continuity, stability, and achievement of a company's operational performance. This study aims to analyze the effects of KPI implementation and workload on employees’ turnover intention at PT Cemerlang Hajar Aswad Tour & Travel Gresik. This study employed a quantitative approach using a survey method involving 40 employees as the research sample. Data were analyzed using multiple linear regression with the assistance of SPSS version 26 through t-test, F-test, and coefficient of determination analysis. The findings reveal that KPI implementation has a negative relationship direction but does not have a significant effect on turnover intention. Meanwhile, workload has a positive and significant effect on turnover intention, indicating that an increase in workload may raise employees’ intention to leave the company. Simultaneously, KPI implementation and workload do not have a significant effect on turnover intention. The coefficient of determination (R Square) value of 9.2% indicates that KPI implementation and workload explain only a small proportion of the variation in turnover intention, while the remaining variation is influenced by other factors outside the research model. This study provides practical implications for the company to improve workload management and evaluate performance measurement systems in order to support employee retention.